EFEKTIVITAS MEDIA TIKTOK DAN INFLUENCER MENDONGKRAK PENJUALAN LIPPIE SERUM RAECCA DIPANDEMI COVID19 - Selvi Ainul Inayah Dwiyanti; Afriza Inda Fitri (Politeknik Bisnis Indonesia, 2021)
This research entitled The Effectiveness of the Social Media of the Tok Team and the Influencer in Boosting Sales Volume Amid the Covid Pandemic19. This research is motivated by the Covid19 pandemic which is a threat to business people in marketing their products. The purpose of this study was to determine the effectiveness level of Tik Tok social media as a place to increase the number of sales during the Covid19 pandemic. This research uses descriptive qualitative methods using literature and interviews with sources to strengthen the results of the research. The result of the research is that Tik Tok social media and Influencers have a role in increasing sales of Lippie Serum products.